Chrome spinels from the Las Águilas mafic-ultramafic intrusion, San Luis Province, Argentina - Ferracutti, Gabriela Roxana (2006)
Two groups of spinel are documented from the mafic-ultramafic rocks of Las Águilas, San Luis Province, Central Argentina. Both spinel types have chromium-aluminum rich cores. However, type I spinel cores are surrounded by chromian-aluminian rims and occur mainly in orthopyroxenites. Type II spinel cores occur mainly in dunites, and show two rims that are compositionally different: rims IIA grade from aluminian-chromite to chromian-magnetites formed by serpentinization, and rims IIB are chromian-aluminium spinel formed during the mylonitization event. Spinel rims type I and type IIA are associated with serpentinized rocks and support the role played by serpentinization processes in the modification of spinel chemistry, which also affected magmatic sulphides and platinum group minerals in the Las Águilas mafic-ultramafic rocks.